The Making of A Gay Muslim: Religion, Sexuality and Identity in Malaysia and Britain by Shanon Shah - Chua Hang-Kuen (Kajian Malaysia, 2020)
It almost goes without saying that being gay and Muslim are perceived as two “incommensurable” (Boellstorff 2007) identities, where one is seen as the antithesis of the other. Gay is often associated with the West, liberalism and secularism; while Muslim is commonly related to the East, conservatism and fundamentalism. Shanon Shah’s The Making of A Gay Muslim: Religion, Sexuality and Identity in Malaysia and Britain juxtaposes two countries, one from the East where Muslims are the majority and one from the West where Muslims are the minority, to investigate this “incommensurability” through an ethnographic approach. Adapted from Shanon Shah’s doctoral thesis, the book offers readers literary and ethnographic insights into the many dimensions – historical, political, social and spiritual – of the making of gay Muslim identities